A Comprehensive Single-Center Analysis of Postoperative Nausea and Vomiting Following Orthognathic Surgery. Issue 2 (10th March 2022) - Pourtaheri, Navid; Peck, Connor J.; Maniskas, Seija; Park, Kitae E.; Allam, Omar; Chandler, Ludmila; Smetona, John; Yang, Jenny; Wilson, Alexander; Dinis, Jacob; Lopez, Joseph; Steinbacher, Derek M.
Abstract : Background: Postoperative nausea and vomiting (PONV) remains a major clinical end-point for directing enhanced recovery after surgery (ERAS) protocols in facial plastic surgery. This study aimed to identify risk factors for PONV and evaluate strategies for PONV reduction in orthognathic surgery patients. Methods: A retrospective cohort study was performed among patients receiving orthognathic surgery at our institution from 2011 to 2018. Patient demographics, surgical operative and anesthesia notes, medications, and nausea/vomiting were assessed for each patient. The amount of opioid analgesia given both perioperatively and postoperatively was recorded and converted into morphine equivalents (MEQ). Stepwise regression analysis was used to identify significant risk factors for PONV. Post hoc analyses were employed to compare PONV among patients based on MEQ dosage and antiemetic prophylaxis regimes. Results: A total of 492 patients were included; mean age was 23.0 years (range: 13–60); 54.4% were female. The majority of patients received concurrent Le Fort I osteotomy, BSSO, and genioplasty (70.1%). During hospitalization, 59.4% of patients experienced nausea requiring antiemetic medications and 28.4% experienced emesis. Stepwise regression yielded Apfel scores ( P  = 0.003) and postoperative opioids ( P  = 0.013) as the strongest predictors of PONV. Post hoc analyses showed that undertreatment with prophylactic antiemetics (based on Apfel) predicted increased PONV (+12.9%, P  = 0.020), and that lower postoperative MEQs (<28.0) predicted decreased PONV (−11.8%, P  = 0.01). Conclusions: The study findings confirm the high incidence of PONV among orthognathic surgical patients and stratify previously reported PONV risk factors. More aggressive utilization of antiemetic medications and decreased dependence on opioid analgesia may decrease nausea/vomiting following orthognathic surgery.